2021
DOI: 10.1007/s00415-020-10385-6
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term psychosocial outcome following mild traumatic brain injury and minor stroke: a direct longitudinal comparison

Abstract: Background and purpose Research suggests comparable long-term psychosocial outcomes following mild traumatic brain injury (mTBI) and minor stroke, but no direct comparison has been made. This study aimed to directly compare psychosocial outcome over time in persons with mTBI and minor stroke. Methods In this multicenter, prospective longitudinal cohort study, community-dwelling persons with mTBI (n = 182) and minor stroke (n = 48) were assessed at 6 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…A further strength is the novel inclusion of both mild stroke and mTBI patients in the model. Both groups often use the same resources for treatment and while past research has shown that mood and cognitive outcomes are comparable between groups ( 8 ), the current study provides further support for this finding with regard to fatigue.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A further strength is the novel inclusion of both mild stroke and mTBI patients in the model. Both groups often use the same resources for treatment and while past research has shown that mood and cognitive outcomes are comparable between groups ( 8 ), the current study provides further support for this finding with regard to fatigue.…”
Section: Discussionsupporting
confidence: 77%
“…Data used in the present study were collected as part of a larger dataset investigating emotional and cognitive recovery following ABI ( 8 ). This study was a multicentre, prospective, longitudinal observational cohort study following participants with mild to moderate TBI, stroke or other forms of ABI over the course of 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…However, it seems that levels and aetiology of depression generally do not differ between stroke or TBI patients (Blicher & Nielsen, 2008 ), nor does their coping style (Herrmann et al, 2000 ). Levels of anxiety can be higher for patients with a stroke, since they can experience fear of stroke recurrence (Chun et al, 2018 ; Verberne et al, 2021 ). Further research should focus on possible differences in the effectiveness of ACT for patients with different types of ABI.…”
Section: Discussionmentioning
confidence: 99%
“…Kangas and McDonald (74) had published an article describing that ACT could be an interesting treatment option for people with ABI-related depression symptoms and Soo et al (75) did this for ABI-related anxiety symptoms. Furthermore, Graham et al (76) performed a case study in which a man with poststroke depressive symptoms and medically unexplained symptoms benefited from an ACT intervention. Besides, Whiting (77) described the results of a pilot RCT in which they compared ACT (n = 10) to befriending therapy (n = 9) for people with severe TBI and psychological distress.…”
Section: Evidence For Actmentioning
confidence: 99%
“…However, it seems that levels and aetiology of depression generally do not differ between stroke or TBI patients (73), nor does their coping style (74). Levels of anxiety can be higher for patients with a stroke, since they can experience fear of stroke recurrence (75,76). Further research should focus on possible differences in the effectiveness of ACT for patients with different types of ABI.…”
Section: Strengths and Limitationsmentioning
confidence: 99%